2017
DOI: 10.1680/jmuen.15.00036
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pedestrian crossing speed – the case of Istanbul

Abstract: Pedestrians, as the most vulnerable road users, are more severely affected when involved in an accident. For this reason, it is important to reduce the risk of pedestrian accidents to increase the safety of highway traffic. The majority of accidents involving pedestrians occur during street crossings where motor vehicles are present. Hence, pedestrians are encouraged to cross safely at crosswalks that are either controlled by a signal or not. Accidents involving pedestrians can be reduced by analysing pedestri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 20 publications
1
7
0
6
Order By: Relevance
“…Goh et al, Tarawneh, and Onelcin and Alver showed in their studies that the mean crossing speed was about 1.31 m/s [13,19,23]. Several studies were found where mean crossing speed was lower than 1.265 m/s [6]. Dündar showed the mean crossing speed in Turkey was 1.20 m/s [6].…”
Section: Descriptive Analysismentioning
confidence: 95%
See 1 more Smart Citation
“…Goh et al, Tarawneh, and Onelcin and Alver showed in their studies that the mean crossing speed was about 1.31 m/s [13,19,23]. Several studies were found where mean crossing speed was lower than 1.265 m/s [6]. Dündar showed the mean crossing speed in Turkey was 1.20 m/s [6].…”
Section: Descriptive Analysismentioning
confidence: 95%
“…Traffic signals are designed for improving the safety of pedestrians. Enough time should be provided in traffic signal phasing so that pedestrians can cross the road comfortably during the green signal phase [6]. This can be possible if the crossing speed of all pedestrian groups is considered at the time of installing traffic signals at crossing locations.…”
Section: Introductionmentioning
confidence: 99%
“…The three transport papers cover a range of planning levels, from extensive road planning to specific aspects of services for use by drivers and pedestrians, in relation to speed humps and street crossings. The findings of Das and Burger (2017), Abdi et al (2017) and Dündar (2017) have relevance at a policy and decision-making level for implementation by practising urban and transportation planners. Results from Ko and Standing (2017) are also relevant to the general public, as well as professional tree specialists.…”
mentioning
confidence: 88%
“…Shortening the distance between speed humps was found to have a direct impact on speed reduction; however, street capacity was also reduced. It is therefore recommended that appropriately distanced speed humps be used to maintain the desired level of service.The paper by Dündar (2017) is the third on the theme of road safety, this time relating to accidents involving pedestrians on street crossings. Individual pedestrian behaviour and their activities while crossing the street were analysed using video footage in combination with an examination of the significance of the different cross walk design features and environmental conditions such as the weather.…”
mentioning
confidence: 99%
See 1 more Smart Citation